"We Want to Build a Network": Professional Experiences of Case Managers Working With Military Families. (August 2019) - Englert, Robyn; Dell'Acqua, Renee; Fitzmaurice, Shannon; Yablonsky, Abigail Marter
Optimizing case management (CM) services increases service member readiness at home and abroad. However, little research has been conducted on the experiences of case managers providing services to military families within the Military Health System. Semistructured qualitative interviews were conducted to explore the professional experiences of case managers to identify factors that may affect care to military families. A total of 53 case managers from military medical treatment facilities (MTFs) varying in size, location, and branch of service were interviewed by telephone to explore their perspectives. Qualitative content analysis was performed. Case managers serve a variety of functions, but specific roles vary between MTFs. Factors that affect CM services for military families were identified: (1) need for pediatric specialization, (2) heavy workload, (3) appropriate staff, (4) patient handoffs, and (5) the role of CM. Recommendations for improving CM services to facilitate the well-being of military families are discussed.